2022
DOI: 10.3389/fcvm.2022.832242
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience With a Large Bore Vascular Closure Device During TAVI Procedure: Features and Predictors of Access-Site Vascular Complications

Abstract: BackgroundsAmong vascular closure devices (VCDs), the novel collagen plug-based MANTA VCD is the first designed for large bore percutaneous access. We aimed to assess the features and predictors of access-site vascular complications in an unselected trans-femoral transcatheter aortic valve replacement (TF-TAVR) population.MethodsPatients undergoing large bore arteriotomy closure with 18F MANTA VCD following TF-TAVR at a large tertiary care center from September 2019 to January 2021 were prospectively analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The MANTA VCD studies showed that the incidence of minor complications varied up to 14%, the incidence of major complications was up to 3%, and life-threatening complications was up to 4% according to the VARC-2 criteria for bleeding, which is comparable to our results ( 9 , 10 , 18 20 ). It is necessary to point out the study by Maisero et al ( 21 ), published in February 2022 as the only research in which the frequency of bleeding complications was classified according to the newest VARC-3 criteria, used in this study. The results showed that the frequencies of mild VARC 1 bleeding complications were higher (14% vs. 4%), while the results in other categories roughly correspond with our study (VARC 2: 1% vs. 2%; VARC 3–4: 2% vs. 5%).…”
Section: Discussionmentioning
confidence: 99%
“…The MANTA VCD studies showed that the incidence of minor complications varied up to 14%, the incidence of major complications was up to 3%, and life-threatening complications was up to 4% according to the VARC-2 criteria for bleeding, which is comparable to our results ( 9 , 10 , 18 20 ). It is necessary to point out the study by Maisero et al ( 21 ), published in February 2022 as the only research in which the frequency of bleeding complications was classified according to the newest VARC-3 criteria, used in this study. The results showed that the frequencies of mild VARC 1 bleeding complications were higher (14% vs. 4%), while the results in other categories roughly correspond with our study (VARC 2: 1% vs. 2%; VARC 3–4: 2% vs. 5%).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, recent evidence suggest that the reported low rates of vascular complications are often not observed in the early roll-in phase of the device in real-world scenarios. 37 Therefore, operator’s experience and centre volumes with individual VCDs should be factored in the decision-making process also for the MANTA device. Furthermore, the MANTA device is not available in many centres and that the overall experience of many skilled TAVR operators with this device is still quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…The striking similitude of predictors of vascular outcomes with use of either of these VCDs corroborate the theory of these factors. Variables such as age [ 34 , 35 ], female gender [ 36 ], severity of calcification or peripheral vascular disease [ 10 , 29 , 36 ], increased sheath size [ 10 ], higher sheath to femoral artery ratio [ 35 , 37 , 38 ], depth of arteriotomy site, and femoral artery size [ 10 , 29 ] play an important role in speculating vascular outcomes and have been shown as predicting variables for vascular outcomes with both VCDs. Calcification in the artery may lead to failure of VCD deployment despite having different mechanisms of failure with each device.…”
Section: Discussionmentioning
confidence: 99%